ANALISIS KELAYAKAN INVESTASI PENAMBANGAN BATUBARA DI PT. CIPTA KRIDATAMA SITE PT. KIM, KABUPATEN BUNGO, PROVINSI JAMBI - Qurratul Ayun; Restu Juniah; Azwardi (Jurnal Teknologi Mineral dan Batubara, 2023)
Indonesia economic development cannot be separated from the role of natural resources, one of the natural resources that currently supports the Indonesian economy is coal. This research was conducted in order to see the prospects for coal mining activities at PT. Cipta Kridatama, site PT. Kuansing Inti Makmur (PT KIM), Bungo Regency, Jambi province through an analysis of management strategies in the form of investment feasibility. The research methodology used is descriptive qualitative in nature referring to quantitative studies, comparative studies (comparisons), and correlational studies. Data collection techniques are carried out by: field research, literature study and secondary data collection such as RKAB of the company. Based on field research, the data obtained included cropline roofs and M4 floor seam, coal strike and dip, overall highwall slope and outcrop area (section). The results of the investment feasibility study were obtained from coal resources based on a stripping ratio (SR) of 1:4.56. From the calculation results, the net present value (NPV) is greater than 0, which is 16,169,241,885, so it can be concluded that this project is considered economical and feasible to mine. The internal rate of return (IRR) is 19.807%, means that PT. Cipta Kridatama was able to return the invested capital with an increase in interest rates reaching 19.807%. Meanwhile, based on the payback period (PBP) calculation, it shows that the time needed for the investment capital to return is 5.6 years, this shows that the payback period is smaller than the project implementation period. The project ratio value (PI)>1 is 3.9537 which means the project is feasible to operate. The calculation has adjusted the discount rate, so the present value (PV) of coal mining PT. Cipta Kridatama of IDR 17,981,921,072.4 according to the discount level. Benefit cost ratio (BCR) value from PT. Cipta Kridatama is 24.66, which means the project is feasible to operate with the profits from the project are greater than the expenses so that the project is acceptable or feasible to continue.